The Influence of Leadership Quality, Organizational Commitment, and Work Culture on Employee Performance at the Manpower and Transmigration Office of West Papua Province - Fdj Saidui️ (SEIKO : Journal of Management & Business, 2022)
This study aims to analyze: 1) The effect of leadership quality, organizational commitment and work culture partially on employee performance, 2) The influence of leadership quality, organizational commitment, and work culture simultaneously on employee performance, and 3) The most dominant variable has an influence on employee performance. employee performance at the Department of Manpower and Transmigration of West Papua Province. The population of this study were all employees of the Department of Manpower and Transmigration of West Papua Province totaling 48 people. Determination of the sample using a saturated sample technique so that the entire population is used as a sample, namely 48 respondents. Data collection techniques using questionnaires and documents, data analysis using multiple linear regression. The results showed that: 1) Leadership quality, organizational commitment, and work culture partially have a positive and significant effect on employee performance, 2) Leadership quality, organizational commitment, and work culture simultaneously have a positive and significant effect on employee performance, 3) Leadership the most dominant influence on employee performance at the Department of Manpower and Transmigration of West Papua Province 4) The results of the coefficient of determination show that 89.8% of employee performance variables can be explained by independent variables: leadership quality, organizational commitment, and work culture, while the remaining 10, 2% is explained by other variables outside this research model. Keywords:Leadership quality, organizational commitment, work culture and employee performance